Characteristics of Species Composition of Causative Agents in Infective Endocarditis - Filonenko, H.; Avetyan, A.; Kramarenko, D.; Salamanina, A.; Guryeva, O.; Romaniuk, O. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Introduction. The frequency of infective endocarditis (IE) in children with congenital heart disease (CHD) is 15– 140 times higher than that in the overall population and varies from 2 to 18% according to different authors. The aim. To define the main groups of causative agents of infective endocarditis in children and adults in order to build up an antibiotic treatment algorithm. Materials and methods. The analysis of examination findings and treatment outcomes in 124 patients was conducted from 2014 to 2019. These patients received medical treatment at the Ukrainian Children`s Cardiac Center (UCCC), Kyiv. The patients were divided into two groups by age: group 1 included children aged from 6 days to 18 years (62 [50.0%]), group 2 comprised adults aged from 18 to 79 years (62 [50.0%]). Results and discussion. Forty-nine isolates were recovered from 124 patients during the analysis of microbiological study results. The frequency of bacterial IE causative agents was 26 (41.9%) in group 1, and 17 (27.4%) in group 2. Comparative analysis of the spectrum of IE pathogens revealed differences in the two study groups. Coagulase-negative staphylococcus was the most common causative agent in group 1 (46.7% of all isolated strains; n = 12) and in group 2 (44.4%; n = 8). Staphylococcus aureus in children was detected in 5 (8.1%) cases, whereas in adults only in 2 (11.1%) cases. Pathogens of the Enterococcus spp. family (E. faecalis) were recovered in both study groups: in 6.5% (n = 2) and 16.6% (n = 3) of the patients, respectively. Gram-negative flora was detected in 3 (9.7%) patients of group 1 and, in 2 (11.1%) patients of group 2. Fungal flora was more commonly found in children (7 [22.6%] cases represented by the Candida family), whereas in adults only 1 (5.6%) case represented by the Mucor family was revealed. Conclusions. Etiological structure of the infective endocarditis pathogens in both groups was represented mainly by gram-positive bacteria, with S. epidermidis (24.5%) being the most essential. The changes were revealed in the species composition of the pathogens in group 1 with fungal microflora dominance: Candida parapsilosis in 9.7%, C. albicans and C. famata in 6.5% of the total number of plated cultures in this group. The difference in surgical operations due to possible IE in both groups was established based on the specific features of operations determined by the age factor.